Long‐term tolerability and efficacy after initial PegIFN‐α addition to dasatinib in CML‐CP: Five‐year follow‐up of the NordCML007 study. (31st August 2021) - Flygt, Hjalmar; Söderlund, Stina; Stentoft, Jesper; Richter, Johan; Koskenvesa, Perttu; Mustjoki, Satu; Majeed, Waleed; Lübking, Anna; Dreimane, Arta; Markevärn, Berit; Stenke, Leif; Myhr Eriksson, Kristina; et al.
Abstract: Objectives: Treatment‐free remission (TFR) has emerged as a treatment goal in chronic myeloid leukemia in the chronic phase (CML‐CP). Attempts to increase proportion of patients achieving TFR include combination of tyrosine kinase inhibitors (TKI) and other drugs. Interferon‐α in addition to TKI has shown promising efficacy but with dose‐dependent toxicity and discontinuations. NordCML007 was initiated to study the efficacy and safety of low dose pegylated IFN‐α (PegIFN‐α) in combination with dasatinib (DAS) in CML‐CP. Methods: Forty patients with newly diagnosed CML‐CP were given DAS upfront. After month 3 (M3) 15 μg/wk of PegIFN‐α was added and increased to 25 μg/wk from M7 until M15. DAS treatment was continued and adverse events and BCR‐ABL1 qRT‐PCR values were reported yearly after M24. Results from M1 to M18 have previously been published, and here we present long‐term data. Results: After 5 years of follow‐up, there were no suspected unexpected serious adverse reactions, no increase in serosal effusions, no disease progressions and no CML‐related deaths. Rates of MR 3.0 (MMR), MR 4.0 and MR 4.5 were 84.6%, 64.1% and 51.3% respectively at M60, and 95% of patients reached MMR at some point during the study. Conclusion: Initial addition of PegIFN‐α to DAS shows good long‐term efficacy without increased toxicity.